SLEEP HEALTH: A NEW PARADIGM FOR SLEEP AND AGING RESEARCH. (11th November 2018) - Buysse, D J; Wallace, M L
Abstract: Good sleep is essential to good health, and poor sleep is associated with poor health outcomes. Sleep-health relationships are particularly salient in older adults: The aging process profoundly affects sleep and circadian regulation, as well as physical, mental, and cognitive health. Sleep-health associations are driven partly by specific sleep disorders (e.g., sleep apnea, insomnia). However, sleep characteristics not defined as 'disorders' also carry risk. For example, sleep duration, quality, efficiency, timing, regularity, and daytime sleepiness have each been linked with poor health outcomes in older adults. Furthermore, each of these characteristics is simultaneously present in all individuals. Recognition of the multidimensional nature of sleep in relation to age-related health outcomes leads to several important questions: Can we define multidimensional sleep health conceptually and psychometrically? Is multidimensional sleep health more strongly related to age-related outcomes than single measures of sleep? How do we best analyze multidimensional sleep health? Our symposium addresses these questions. Dr. Buysse will provide an introduction and conceptual framework for sleep health in aging; Dr. Stone will discuss applications of multidimensional sleep health to age-related outcomes including functional limitations and performance; Dr. Buxton will discuss modifiable facets of sleep health that predict cardiometabolic risk in midlife and older adults; Dr. Carroll will examine the role of poor sleep health in phenotypic and biologic indicators of accelerated aging; finally, Dr. Wallace will demonstrate traditional and cutting-edge statistical approaches to studying multidimensional sleep health, exemplified by applications to mortality risk in large aging cohorts.